Moments, sceneries, and subjects in the constituent production. critical approaches to constitutional process in 90’s (2006)
In front of these realities, the convocation to the Constituent National Assembly was erected as the great political moment for the consolidation of a new society project characterized by a true democratic "eticidad". The narratives of the democracy participativa and the consolidation of the peace were constituted in the new securities for the legitimation of the nascent social project. The setting in scene of these narratives allowed the convergence of the diverse social actors in the alternative of summoning to the primary constituent for the formulation of a new political pact. In fact, the idea of the ANC was protected with different shades for diverse social and political forces that you/they went from the most progressive tendencies to the most conservative. However, he/she cannot forget that the most interested actor in the Construction of a new Political Letter for the Colombians was the executive.